Closure duration as an acoustic correlate of the word-initial singleton/geminate consonant contrast in Kelantan Malay. (September 2016) - Hamzah, Mohd Hilmi; Fletcher, Janet; Hajek, John
Abstract: Closure duration has been established cross-linguistically as the universally most reliable and consistent acoustic feature of consonant gemination. In this study, we conduct an acoustic phonetic analysis of the word-initial singleton/geminate consonant contrast in Kelantan Malay (KM) in order to explore the extent to which closure duration marks such a contrast in this Malay variety. KM is particularly unusual among the world׳s languages in that the contrast is restricted to word-initial position. A corpus of elicited materials consisting of singleton/geminate voiceless stops, voiced stops and sonorants were produced in words in isolation (i.e., utterance-initial position) and in a carrier sentence (i.e., utterance-medial position) by sixteen native speakers of KM. Results show that closure duration is a robust acoustic correlate of the consonant contrast in KM, i.e., word-initial geminates in KM are always associated with significantly longer closure duration than their corresponding singletons. The closure duration differences between singletons and geminates are also similar across utterance positions (at least for voiced stops and sonorants). In utterance-medial contexts, the effect is particularly strong in the closure duration of voiceless stops. Overall, closure duration is indeed a highly robust acoustic marker for this cross-linguistically rare word-initial consonant contrast in KM. Highlights: Closure duration is a robust acoustic correlate of the word-initial contrast. Word-initial geminates are much longer than their corresponding singletons. The degree of durational contrast is essentially similar across utterance positions.